A relaxation model of phonon gas interaction with an external field - PIEKARSKI, S. (Archives of Acoustics, 1991)
In the paper, a kinetic model of interactions of optical and acoustical phonons is discussed, basing on four life-times. Equations of non-diffusive transfer of heat perturbations, induced by an external field acting upon an assembly of optical phonons, are derived form the proposed model.